Differentiation of committed osteoblast progenitors by octacalcium phosphate compared to calcium-deficient hydroxyapatite in Lepr-cre/Tomato mouse tibia. (1st April 2022) - Okuyama, Kyosuke; Shiwaku, Yukari; Hamai, Ryo; Mizoguchi, Toshihide; Tsuchiya, Kaori; Takahashi, Tetsu; Suzuki, Osamu
Abstract: This study aimed to investigate the accumulation and differentiation of mesenchymal stem cells (MSCs) around octacalcium phosphate (OCP) compared with those around calcium-deficient hydroxyapatite (CDHA), a material obtained through hydrolysis of the original OCP. Leptin receptor (Lepr)-expressing bone marrow-derived MSCs around the OCP and CDHA were pursued utilizing genetically modified Lepr- cre /Tomato mice. OCP and CDHA granules were implanted into the tibia defect of the mice for 10 weeks and subjected to histomorphometric and immunohistochemical analyses. The structural properties of OCP and CDHA after inoculation into mouse subcutaneous tissue (until 4 weeks) or culture mediums (14 days) were analyzed using physicochemical techniques. In vitro osteoblastic differentiation of primary MSCs was examined with the materials for 14 days. While Lepr- cre /Tomato positive cells (red) accumulated around both OCP and CDHA, Lepr and osteocalcin double-positive osteoblastic cells (yellow) were significantly more abundant around OCP than around CDHA in the early implantation period. OCP enhanced the osteoblastic differentiation of MSCs more than CDHA in vitro. Physicochemical and structual analyses provided evidence that OCP tended to convert to the apatitic phase in the tested physiological environments. The higher osteoconductivity of OCP originated from a capacity-enhancing osteoblastic differentiation of committed osteoblast progenitors in bone marrow accompanied by OCP hydrolysis. Statement of significance: MSCs play a key role in bone regeneration through osteoblastic differentiation. Calcium phosphates have been widely applied as bone substitute materials, and OCP has a better ability to promote osteoblast differentiation of MSCs than that of HA in vitro. However, it is not clear how MSCs accumulate in the bone marrow and differentiate into osteoblasts during bone regeneration in vivo. In this study, we focused on the leptin receptor, a marker of bone marrow-derived MSCs. Using genetically modified mice labeled with the red fluorescent protein Tomato, we observed the accumulation of MSCs around calcium phosphates implanted in tibia bone defects and their differentiation into osteoblasts. Graphical abstract: Image, graphical abstract